The role of macroeconomic, policy, and forecaster uncertainty in forecast dispersion - LI, You (Institutional Knowledge at Singapore Management University, 2017)
We explore the role of uncertainty in explaining dispersion in professional forecasters’ density forecasts of real output growth and inflation. We consider three separate notions of uncertainty: general macroeconomic uncertainty (the fact that macroeconomic variables are easier to forecast at some times than at others), policy uncertainty, and forecaster uncertainty. We find that dispersion in individual density forecasts is related to overall macroeconomic uncertainty and policy uncertainty, while forecaster uncertainty (which we define as the average in the uncertainty expressed by individual forecasters) appears to have little role in forecast dispersion.